A Smartphone-based Medication Self-management System with Real-time Medication Monitoring - Hayakawa, M.; Uchimura, Y.; Omae, K.; Waki, K.; Fujita, H.; Ohe, K. (Applied Clinical Informatics, 2013)
Background: Most patients cannot remember their entire medication regimen and occasionally forget to take their medication.Objectives: The objective of the study was to design, develop, and demonstrate the feasibility of a new type of medication self-management system using smartphones with real-time medication monitoring.Methods: We designed and developed a smartphone-based medication self-management system (SMSS) based on interviews of 116 patients. The system offered patients two main functions by means of smartphones: (1) storage and provision of an accurate, portable medication history and medication-taking records of patients; and (2) provision of a reminder to take medication only when the patient has forgotten to take his/her medication. These functions were realized by two data input methods: (a) reading of prescription data represented in two-dimensional barcodes using the smartphone camera and getting the photographic images of the pills; and (b) real-time medication monitoring by novel user-friendly wireless pillboxes.Results: Interviews suggested that a pocket-sized pillbox was demanded to support patient’s medication-taking outside the home and pillboxes for home use should be adaptable to the different means of pillbox storage. In accordance with the result, we designed and developed SMSS. Ten patients participated in the feasibility study. In 17 out of 47 cases (36.2%), patients took their medication upon being presented with reminders by the system. Correct medication-taking occur-rence was improved using this system.Conclusions: The SMSS is acceptable to patients and has the advantage of supporting ubiquitous medication self-management using a smartphone. We believe that the proposed system is feasible and provides an innovative solution to encourage medication self-management.Citation: Hayakawa M, Uchimura Y, Omae K, Waki K, Fujita H, Ohe K. A smartphone-based medication selfmanagement system with real-time medication monitoring. Appl Clin Inf 2013; 4: 37–52http://dx.doi.org/10.4338/ACI-2012-10-RA-0045
Keywords: Self-management; mobile phone; medication adherence; physiologic monitoring; eHealth systems